Stress recognition using photoplethysmogram (PPG) signal incorporating gender and age variability - Abd Halim, Noor Hafizah Azlin; Sidek, Khairul Azami; Mansor, Hasmah (Malaysia Technical Scientist Association, 2019)
The present study suggested a new method of stress recognition using photopletysmogram (PPG) signal incorporating gen-der and age variability. PPG devices are using in this study due to its advantages such as low cost solution, portable, low power consumption and also easy to handle. Mainly, this study involves a total of 30 subjects from different gender and age group. The pulse oximetry is used to obtain PPG signals. The normal signal was collected when the subject are in the resting condition. The subjects then go through a stressor test in order to record the physiological changes and will be mark as a stress signal. Then, all the data were extracted and classified using classification techniques to know the differences between normal and stress signal. Based on the experimentation results, the peak value differences and Cardiod area differences of normal and stress conditions for female are higher than male. While, for age variability, the subjects from Group B (20-29 years old) shows the highest value as compared to other age groups. Therefore, the findings prove that the PPG signal are capable to recognize the stress recognition incorporating gender and age variability.